2014
DOI: 10.1016/j.micpath.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Brucella alters the immune response in a prpA-dependent manner

Abstract: Brucellosis, a disease caused by the gram-negative bacterium Brucella sp, is a widespread zoonosis that inflicts important animal and human health problems, especially in developing countries. One of the hallmarks of Brucella infection is its capacity to establish a chronic infection, characteristic that depends on a wide repertoire of virulence factors among which are immunomodulatory proteins such as PrpA (encoding the proline racemase protein A or hydroxyproline-2-epimerase), involved in the establishment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 37 publications
(38 reference statements)
0
14
0
3
Order By: Relevance
“…B-cell proliferation is initiated by the secretion of Brucella virulence factor prpA that interact with macrophages and release several soluble factors necessary for establishing chronic infection (Spera et al, 2006 , 2013 ). In addition to this, Brucella change the cytokine level of IFN-γ, TNF-α, IL-10 and TGFβ1 in the early stages of brucellosis in a prpA dependent manner (Spera et al, 2014 ). Recent studies clarify the roles of Btp1/TcpB, Br-LPS and PrpA as being significant immunomodulatory molecules with the ability to interplay with host immune mechanisms.…”
Section: Brucella Impressive Mechanisms To Evade Adaptive Immentioning
confidence: 99%
“…B-cell proliferation is initiated by the secretion of Brucella virulence factor prpA that interact with macrophages and release several soluble factors necessary for establishing chronic infection (Spera et al, 2006 , 2013 ). In addition to this, Brucella change the cytokine level of IFN-γ, TNF-α, IL-10 and TGFβ1 in the early stages of brucellosis in a prpA dependent manner (Spera et al, 2014 ). Recent studies clarify the roles of Btp1/TcpB, Br-LPS and PrpA as being significant immunomodulatory molecules with the ability to interplay with host immune mechanisms.…”
Section: Brucella Impressive Mechanisms To Evade Adaptive Immentioning
confidence: 99%
“…To achieve this, the bacterium has the capacity to translocate to the host cells a plethora of proteins that alter either the normal trafficking of the intracellular bacteria or the immune response triggered by the infection (3,10). PrpA is one of these effector proteins, and we have previously shown that this virulence factor is involved in the modulation of the immune response, acting on macrophages and triggering a polyclonal B-cell proliferation response that allows the bacterium to establish a persistent infection (5)(6)(7). How the protein is targeted to the plasma membrane of the host cell after its translocation from the Brucella-containing vacuole has not been elucidated until now.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoglobulin quantification. The titers of specific immunoglobulins against Brucella were determined by indirect enzyme-linked immunosorbent assay (ELISA) (6). Briefly, ELISA MaxiSorp plates (Nunc, USA) were sensitized with 0.4 g/well of Brucella abortus total protein extracts overnight and blocked for 2 h with 1% BSA in PBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brucellaceae are wide spread zoonotic intracellular pathogens with the capacity to evade and modulate the immune response of the infected hosts, a hallmark of their infectious processes [1]. Many of these immunomodulatory activities are achieved by a plethora of virulence factors that are able to manipulate the immune system to its benefit, promoting bacterial proliferation and the establishment of the chronic infectious phase [2][3][4][5][6][7]. Brucella is considered a pathogen with a stealthy strategy, meaning that is able to avoid a strong immune response "hiding" its pathogen-associated molecular patterns (PAMPs).…”
Section: Introductionmentioning
confidence: 99%